THE INFLUENCE OF INFLATION AND EXCHANGE RATES ON INDONESIA'S ECONOMIC GROWTH - Hasanudin Hasanudin (Sean Institute, 2022)
The goal of this study was to examine the impact of inflation and exchange rates on Indonesian economic growth. This study makes use of time series data from 20 13 -20 22. The analysis approach employs several linear regression equations, the coefficient of determination, and statistical tests (t and F tests) with the Microsoft Excel application. Secondary data was acquired from Bank Indonesia and the Central Bureau of Statistics. According to the study's findings, inflation has a negative and considerable impact on Indonesia's economic growth. Additionally, the exchange rate has a negative but not statistically significant impact on economic growth. This study has significant significance for the government and commercial stakeholders in developing economic policies and risk management.